Analysis Of Magnus Effect Toward The Shaft Of Vetical Axis Hydro Turbine H-Darrieus - Irfan Syarief Arief; Amiadji; I Putu Gedhe Adhi Darsana; Achmad Baidowi (International Journal of Marine Engineering Innovation and Research, 2023)
One way to fight climate change is making a transition from fossil fuel powered energy into renewable energy. In Indonesia the government have the national energy mix prediction which state that in 2050 58% Indonesian energy source will be renewable. The biggest source of renewable energy in Indonesia come from marine source. One sources of marine energy are tidal currents that can be harness by using hydrokinetic turbine. The goal to be solved is to determine the effect of magus force toward the turbin shaft. Shaft rotation speed and fluid velocity will be determined as the variation. The method used is computational fluid dynamic using fine marine numeca software to determine magnus force magnitude and mdsolids software to calculate the maximum bending moment after the magnus force applied. The results is magnus force just increase the minimum required diameter of turbine shaft by 0.26% and the corresponding safety factor is 1.889 more than 1.0 thus there is no need to replace or strengthen the existing turbine shaft.